2012
DOI: 10.1177/0272431612449385
|View full text |Cite
|
Sign up to set email alerts
|

Time for “The Talk” . . . Now What? Autonomy Support and Structure in Mother-Daughter Conversations About Sex

Abstract: This study explored how mothers communicated with their young adolescent daughters about the high-stakes topic of sex, as well as more everyday topics, from a Self-Determination Theory perspective. Mothers and their 11- to 14-year-old daughters (44 dyads) participated in two conversations and reported on their experiences. In the everyday conversation, maternal autonomy support was positively related to daughters’ experience, engagement, and desire for additional conversations. In the sex conversation, materna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
3
27
0
3
Order By: Relevance
“…When mothers provided information and feedback, daughters were more engaged and desired further conversations about sex (Mauras, Grolnick, & Friendly, 2013). However, most mothers admitted they only discussed sex-related issues at their daughters’ initiation and they did not talk about sex unless asked (Baier & Wampler, 2008; Elliott, 2010a).…”
Section: Resultsmentioning
confidence: 99%
“…When mothers provided information and feedback, daughters were more engaged and desired further conversations about sex (Mauras, Grolnick, & Friendly, 2013). However, most mothers admitted they only discussed sex-related issues at their daughters’ initiation and they did not talk about sex unless asked (Baier & Wampler, 2008; Elliott, 2010a).…”
Section: Resultsmentioning
confidence: 99%
“…One possible candidate for this suppressing variable could be the nature of maternal behavior when sensitive topics such as distressing events are under consideration. Mauras, Grolnick, and Friendly () found that direct questioning and guidance were preferred by girls when sensitive issues (e.g., sexual activity), as opposed to everyday topics, were under consideration. In this case autonomy‐supportive mothers who encourage the exploration of their children's ideas might be less likely to provide conditions that would promote child knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to research on supports for relatedness and autonomy, there is less research on parental structure, although a relevant study on teachers providing structure to adolescents did predict more student behavioral engagement (Jang, Reeve, & Deci, 2010). Further, studies are beginning to show that parental structure is related to important motivational and developmental outcomes in different life domains, including academic competence, engagement, and performance (e.g., Farkas & Grolnick, 2010;Grolnick, Raftery-Helmer, Flamm, Marbell, & Cardemil, 2015), feelings of competence during unsupervised time (e.g., activities with friends in the absence of parents; Grolnick et al, 2014), and engagement and positive experiences during parent-child conversations about sensitive topics such as sexuality (Mauras, Grolnick, & Friendly, 2013). In contrast, parental chaos has been found to relate to problem behaviors such as substance use and delinquency (Skinner et al, 2005).…”
Section: Structurementioning
confidence: 99%